Peran Audit Delay, Debt Default, Dan Pertumbuhan Perusahaan Terhadap Opini Audit Going Concern : Reputasi Auditor Sebagai Variabel Moderasi - Lavida Melia Febrianti; Dwi Suhartini (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aimed to analyze the effect of audit delay, debt default and company growth on going concern audit opinion with auditor reputation as a moderating variable. This research is a quantitative study using logistic regression with the SPSS 26 analysis tool. The sample of this research is the mining sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020. The research sample was taken using purposive sampling method which resulted in 96 samples. Based on the hypothesis test, this research reveals that mining sub-sector companies listed on the Indonesia Stock Exchange during 2018-2020 will receive a going concern audit opinion if the company fails to pay its debts. On the other side, audit delay and company growth do not cause the company to accept a going concern audit opinion. The reputation of the auditor has not been able to encourage the acceptance of a going concern audit opinion. Keywords : audit delay, debt default, compony growth, reputasi auditor, going concern audit opinion